Phenolic compounds extracted by acidic aqueous ethanol from berries and leaves of different berry plants - Tian, Ye; Liimatainen, Jaana; Alanne, Aino-Liisa; Lindstedt, Anni; Liu, Pengzhan; Sinkkonen, Jari; Kallio, Heikki; Yang, Baoru (Food chemistry, 2017)
•Fruits and leaves of berry species have great potential as bioactive ingredients of food.•A food-grade method was used to extract phenolic compounds from berries and leaves.•Thorough information of phenolic compounds of berries and leaves of different species.•Other aromatic compounds shall be considered when evaluating safety of some materials.•The research provides important guidance for application of the materials. Phenolic compounds of berries and leaves of thirteen various plant species were extracted with aqueous ethanol and analyzed with UPLC-DAD-ESI-MS, HPLC-DAD, and NMR. The total content of phenolics was consistently higher in leaves than in berries (25–7856 vs. 28–711mg/100g fresh weight). Sea buckthorn leaves were richest in phenolic compounds (7856mg/100g f.w.) with ellagitannins as the dominant compound class. Sea buckthorn berries contained mostly isorhamnetin glycosides, whereas quercetin glycosides were typically abundant in most samples investigated. Anthocyanins formed the dominating group of phenolics in most dark-colored berries but phenolic acid derivatives were equally abundant in saskatoon and chokeberry berries. Caffeoylquinic acids constituted 80% of the total phenolic content (1664mg/100g f.w.) in bilberry leaves. B-type procyanidins and caffeoylquinic acids were the major phenolic compounds in hawthorn and rowanberry, respectively. Use of leaves of some species with prunasin, tyramine and β-p-arbutin, may be limited in food applications.